Improving Personnel Performance at Bandung Staff and Army Command School (SESKOAD) - Yosandi Yulius (Journal of Accounting and Finance Management, 2021)
The purpose of this study was to determine and analyze: The Effect of Workload and Work Environment on Personnel Performance at the Army Command and Staff College (SESKOAD) Bandung. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this study is the personnel at the Army Command and Staff School (SESKOAD) Bandung with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the Workload and Work Environment had an effect on the Performance of Personnel at the Army Staff and Command School (SESKOAD) Bandung simultaneously and partially. However, partially the dominant workload affects the performance of the personnel rather than the work environment. Because the workload is more dominant in influencing performance, it becomes the first priority in improving the performance. Therefore, the Bandung Army Staff and Command School (SESKOAD) is advised to improve working conditions and atmosphere, so that they are able to work more professionally.